2001
DOI: 10.1007/s004410100351
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of MUC1, an apical membrane glycoprotein, in mammary epithelial cells at the resolution of the electron microscope: implications for the mechanism of milk secretion

Abstract: The distribution of the glycoprotein, mucin 1 (MUC1), was determined in lactating guinea-pig mammary tissue at the resolution of the electron microscope. MUC1 was detected on the apical plasma membrane of secretory epithelial cells, the surface of secreted milk-fat globules, the limiting membranes of secretory vesicles containing casein micelles and in small vesicles and tubules in the apical cytoplasm. Some of the small MUC1-containing vesicles were associated with the surfaces of secretory vesicles and fat d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 73 publications
0
27
0
Order By: Relevance
“…Studies have shown that epithelial Muc1/MUC1 facilitates mucosal wound healing by enhancing cell migration and proliferation, protecting against apoptosis and mediating expression of mucosal modulators (35). In most epithelial-derived cancer cells, MUC1 is overexpressed and loses its apical polarity (36,37). In various adenocarcinoma including ESCC, MUC1 overexpression is correlated with tumor growth, lymph node metastasis and resistance to apoptosis (38), involved in multiple cancer-associated pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that epithelial Muc1/MUC1 facilitates mucosal wound healing by enhancing cell migration and proliferation, protecting against apoptosis and mediating expression of mucosal modulators (35). In most epithelial-derived cancer cells, MUC1 is overexpressed and loses its apical polarity (36,37). In various adenocarcinoma including ESCC, MUC1 overexpression is correlated with tumor growth, lymph node metastasis and resistance to apoptosis (38), involved in multiple cancer-associated pathways.…”
Section: Discussionmentioning
confidence: 99%
“…CD86 was also identified on the surface of vesicles derived from both the colostrum and mature milk of four of eight individuals at moderate levels. MUC-1, a glycoprotein that is present in large amounts in MFG (22), was detected in these vesicle fractions (Fig. 2B).…”
Section: Phenotypic Analysis Of the Vesiclesmentioning
confidence: 98%
“…It has been reported that BTN and XOR are expressed in constant molar proportions in bovine MFGM and these proportions vary with breed and stage of lactation. Particularly, XOR as a homodimer may simultaneously bind two BTN molecules and therefore be responsible for the observed accumulation of BTN molecules on budding membrane areas (Mather et al 2001). A likely explanation for the up-regulation of XOR during lactation is the high cellular demand for this structural molecule, since it is continuously lost from the cell with each budding fat droplet.…”
Section: Discussionmentioning
confidence: 99%